PERSEPSI DUKUNGAN SOSIAL DAN KEMAMPUAN KOMUNIKASI INTERPERSONAL PADA PASIEN TUBERKULOSIS PARU DI DENPASAR - Ningrum, Mira Juwita Surya; Suarya, Luh Made Karisma Sukmayanti (Jurnal Psikologi Udayana, 2014)
Interpersonal communication is a skill to answer all individu needs in positive way in the field of communication. However, interpersonal communication often encountered obstacle, which can be caused by a disease, such as Pulmonary Tuberculosis. Pulmonary Tuberculosis is a direct infectious disease caused by the bacteria Mycobacterium tubercolusis. Pulmonary Tuberculosis patients experience anxiety, fear and shame that inhibit interpersonal communication, in which pulmonary tuberculosis patients are difficult to communicate feeling and thought related to disease experienced. One of the handling method is social support, but the emergence of anxiety, fear, and embarrassment against other individuals, causing the perception of social support from Pulmonary Tuberculosis patients. Based on this background, the researcher propose the issue of whether there is a relationship between perception of social support and interpersonal communication skill in pulmonary tuberculosis patients in Denpasar.   This research is quantitative methods and hypothesis testing was done by using Pearson's Product Moment analysis. Subjects consisted of 83 Pulmonary Tuberculosis patients in Denpasar. Data collection used two scales to measure perception of social support and interpersonal communication skill . Scale’s items have been tested for validity and reliability. Perception of social support scale showed 46 valid items with reliability of 0,957, while interpersonal communication skill scale showed 38 valid items with reliability of 0,926. Based on the data analysis, data is linear and normal , so the Pearson 's Product Moment test can be done. Based on the research results, correlation coefficient between  two variables is 0,759 with significance level of  0,000. Thus, it can be concluded that there is a positive relationship between perception of social support and interpersonal communication skill in patients with pulmonary tuberculosis in Denpasar.   Keywords: Perception of Social Support, Interpersonal Communication Skill, Pulmonary Tuberculosis